The potential of youth and older people’s participation in the development of creative industries in Kazakhstan and the directions of its activation - Assanova, M.K.; Khussainova, Zh.S.; Kankulov, M.K.; Zhartay, Zh.M.; Bektleyeva, D.Ye. (BUKETOV BUSINESS REVIEW, 2024)
Object: To assess the potential for diversification of socio-economic participation of youth and older people in the development of creative industries of the Republic of Kazakhstan. Methods: The research uses methods of indirect (questionnaire) selective sociological survey with the allocation of individual focus groups, graphical interpretation of the answers received and their comparative analysis. Findings: The object of the study were the largest cities of Kazakhstan: Astana, Almaty, Shymkent, Karaganda. Four focus groups were surveyed: youth, the elderly, representatives of creative industries, and government agencies. A set of specialized state support measures has been proposed to enhance the socio-economic potential of young people and the elderly. Conclusions: The study shows that in Kazakhstan, creative industries are more developed in cities than in rural areas. There are certain infrastructural foundations and a creative environment for the formation of creative clusters, especially in the cities of Almaty and Astana. The degree of involvement of young people and the elderly in production and consumption has an impact on the diversification of creative industries. It was revealed that young people are actively involved in the production and consumption of creative products, more than half of the youth see themselves in the creative business. Older people also participate in the production and consumption of products from creative industries, but to a lesser extent, their involvement in the production process is especially low, despite having significant potential and experience of creative activity in the past, as well as the activity of visiting creative spaces and creative leisure activities. Among the barriers limiting the development of creative industries in Kazakhstan, financial constraints have the greatest weight. Representatives of the creative industries show a more complex picture of the real situation in the creative sector and the low effectiveness of government support measures than representatives of government agencies. Representatives of the existing creative industries and the elderly prefer creative types of creative activities, young people and representatives of government agencies show more interest in innovative and informational types of creative activities.